EFFECT OF POLYETHYLENE GLYCOL SUPPLEMENTATION ON IN VITRO NITROGEN DIGESTIBILITY OF LEUCAENA SHRUB LEGUM SPECIES AND SIGNAL GRASS (BRACHIARIA DECUMBENS) - RUSDI, RUSDI (Majalah Ilmiah Peternakan, 2012)
SUMMARY An in vitro study was conducted to investigate the effect of polyethylene glycol (PEG) supplementation on in vitro nitrogen digestibility in shrub species legume and grass. The nitrogen digestibility of varied correspondingly to their nutrient and condensed tannin (CT) content. Leuceana species with a lower CT tended to have higher in vitro nitrogen digestibility (IVND) and rate of ammonia-N production. PEG consistently increased IVND and the rate of ammonia-N production. The increased values were from 30.7 to 71.2% and 52.3 to 93.6 mg/d for nitrogen digestibility and the rate of ammonia-N production respectively when the inclusion rate of PEG was elevated from 0 to 200 mg/g sample of forages. Leucaena species with a high CT content required more PEG to neutralize negative effect of tannins on nitrogen digestibility than did species with low tannin content. PEG, however, had no effect on the nitrogen digestibility of signal grass.